Chemical composition and antimicrobial activity of the essential oil from leaves of Magnolia coriacea (Hung T. Chang & B. L. Chen) figlar growing in Vietnam - Ha, Chu Thi Thu; Thanh, Bui Van; Thuy, Dinh Thi Thu (Academia Journal of Biology, 2020)
Leaf essential oil of Magnolia coriacea (Hung T. Chang & B. L. Chen) Figlar growing wild in the Bat Dai Son Nature Reserve, Ha Giang Province, Viet Nam was obtained by hydrodistillation and its chemical composition was analyzed using GC/MS. In total, 45 compounds were detected in the essential oil, accounting for 87.1% of the oil, in which 37 compounds were identified accounting for 66.9%. Bicyclogermacrene (12.6%) and spathulenol (17.0%) were the main components of the leaf essential oil of M. coriacea. Antimicrobial activity of the essential oil sample was tested against three microorganism strains using an agar disk diffusion method. The results show that the inhibitory zone diameters ranged from 8.5 to 20.5 mm. Median inhibitory concentration (IC50) and minimum inhibitory concentration (MIC) of the essential oil was determined using microdilution broth susceptibility assay against seven test microorganism strains. Bacillus subtilis had the highest sensitivity with IC50 and MIC values of 185.9 and 512 µg/mL, respectively.